2008
DOI: 10.1111/j.1365-2044.2008.05491.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of conscious sedation using propofol and remifentanil for tension‐free vaginal tape insertion

Abstract: Tension-free vaginal tape insertion is a recommended treatment for stress incontinence. There is evidence that intra-operative testing of continence by asking patients to cough may improve outcomes, but an optimal sedation regimen has not been determined. We prospectively evaluated the effectiveness of propofol and remifentanil infusions in 25 patients using pre-and postsedation peak cough pressures and pain scores. Patient satisfaction was assessed using the Iowa Satisfaction with Anaesthesia Score (ISAS). Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The propofol/alfentanil regimen that we used impair safety, which also was confirmed for incontinence surgery in which target-controlled infusion of propofol and remifentanil resulted in apneic episodes, reduced respiratory rate, oxygen desaturation, and the need for close monitoring. 2 Our use of the same mixtures for gynecological treatment as for burn care 19 , display problems with generalizability, and to ensure safety, tuning of the PCS system is needed. 8 Usually surveys describe a preset loading dose that is infused before the patient uses the PCS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The propofol/alfentanil regimen that we used impair safety, which also was confirmed for incontinence surgery in which target-controlled infusion of propofol and remifentanil resulted in apneic episodes, reduced respiratory rate, oxygen desaturation, and the need for close monitoring. 2 Our use of the same mixtures for gynecological treatment as for burn care 19 , display problems with generalizability, and to ensure safety, tuning of the PCS system is needed. 8 Usually surveys describe a preset loading dose that is infused before the patient uses the PCS.…”
Section: Discussionmentioning
confidence: 99%
“…Local anesthesia is widely used, sometimes combined with propofol alone, 1 or propofol and remifentanil. 2 The need to improve effectiveness and quality has led to the more extensive use of propofol. Moderate sedation has also been claimed to be an alternative to general anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…We chose to add sedation compared to local para urethral infiltration only, since this has been widely accepted as an effective type of anesthesia in terms of analgesia and patient satisfaction. It also allows for the ability to create an effective cough during surgery . Furthermore, Abdel‐Fattah reported that 29% of the patients did not accept an Ajust® procedure solely under local anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…This a 2 -adrenergic receptor agonist offers a unique ''cooperative sedation,'' anxiolysis, and analgesia, with no respiratory depression [14,15]. Dexmedetomidine is usually administered as a continuous infusion, which makes it easy to titrate, and it is associated with a predictable and stable hemodynamic response [6,7]. However, care and precautions should be taken when it is administered to patients who are volumedepleted, vasoconstricted, or have severe heart block [14], as dexmedetomidine can cause severe hypotension and bradycardia.…”
Section: Discussionmentioning
confidence: 99%
“…Later, epidural anesthesia gained popularity and seemed to be the right choice, as it allowed patients to cough and be pain free at the same time. An optimal regimen would provide complete analgesia and sedation during tape insertion and an orientated patient able to cooperate with incontinence testing [6].…”
Section: Introductionmentioning
confidence: 99%